Clinical efficacy of acupoint embedment in weight control: A systematic review and meta-analysis. Issue 36 (September 2018) - Cho, William C.; Li, Ching; Chen, Hai-Yong
Abstract: Introduction: Acupoint embedment, a modified acupuncture technique, is gaining its popularity in weight control in adult obesity or overweight nowadays. The objective of this study was to investigate the clinical efficacy of acupoint embedment in weight control of adult obesity or overweight by systematically assess available randomized controlled trials (RCTs) and analyze the integrated findings. A total of 529 literatures were initially searched from the databases. Five RCTs in assessing the effect of acupoint embedment versus sham control group were identified. Results: A total of 219 subjects in the intervention group and 206 subjects in the control group from 5 eligible studies were eventually included in this meta-analysis. Mean body mass index (BMI) decreased 0.94 kg/m 2 (95% confidence interval [CI]: −1.56 to −0.32, P  = .003) more in acupoint embedment group than the sham control group. Meanwhile, subjects received acupoint embedment had 2.97 kg (95% CI: −4.44 to −1.49, P  < .0001) decrease in mean body weight more than in sham control group. Both parameters were statistically significant. Adverse events including bruise, soreness and cramp, patchy skin induration, erythema were reported, yet none involved hospitalization or mortality. Interestingly, stomach meridian and spleen meridian involved in all 5 studies. Conclusion: This meta-analysis showed that acupoint embedment was more effective in weight control than the sham control group. Together with its convenience and low cost, acupoint embedment may be considered as an alternative treatment in weight control.